MINAT MAHASISWA TERHADAP PROFESI GURU - Faruq Abdur Rouf; Amos Neolaka; Dadang Suyadi (LPPM Universitas Negeri Jakarta, 2016)
This study aims to reveal the level of student interest in technical education building of the FT UNJ the teaching profession, the study was conducted starting from March until July, 2016. The study was conducted in Building Engineering Study Program, this research uses descriptive qualitative method, namely data collection techniques by spreading questionnaires and interviews as the reinforcement of the answers to the questionnaire. The results of this study are students of Technical Education Building has a high interest in the teaching profession, they considered that the teaching profession is a noble job, and for that assessment increases the pleasure of students in teaching, and all it's the result that students PTB FT UNJ have high interest in the teaching profession